The Literature on Open Government in Spanish. Analysis of the Dynamics of Production and Citation - Barria-Traverso, D; Gonzalez-Bustamante, B (UNIV AUTONOMA CIUDAD JUAREZ, INST CIENCIAS SOCIALES & ADM, 2019)
Open government has become one of the concepts that most recently attracted professionals and academics dedicated to public administration. Likewise, it is possible to notice the appearance of a growing volume of academic works dedicated to analyzing the concept and experiences of open government in the region. This paper analyzes the academic production in Spanish on open government. For this, texts published in specialized journals between 2009 and 2015 are identified. It characterizes the main publication channels, indexing levels of journals that publish articles of the topic as well as bibliographic references. This is complemented by a citation network analysis and a statistical model that evaluates determinants of centrality in the network. One of the findings is that non-academic documents are more likely to be central in the citation network.